Shear rate dependence on mixing and compaction temperatures - Saboo N.; Kumar P.; Gupta A.; Ranjeesh R. (My University, 2025)
This study evaluates the effect of shear rate on the viscosity of asphalt binders, and uses it to propose a unique approach for assessing the mixing and compaction temperatures. Four different asphalt binders including VG 10, VG 30, PMB 1 and PMB 2 were chosen. Dynamic shear rheometer was used to conduct shear rate sweep test at temperatures ranging from 10–70°C. Viscosity master curves were plotted at seven different reference temperatures for each binder and Cross model was used to fit the master curve. The parameters of the Cross model in conjunction with the desired viscosity values for mixing and compaction were used to evaluate the appropriate processing temperatures through the proposed approach. The study concludes that shear rate has a dominant effect on the viscosity of asphalt binders. Polymer modified binders shows higher shear thinning behavior as compared to the conventional viscosity graded binders. Cross model can be successfully used to trace the viscosity shear rate relationships at different reference temperatures. The new methodology showed that at higher shear rates, which is commonly employed during construction, a lower mixing and compaction temperature can be suggested for modified binders. The new methodology gives flexibility to the designer to choose appropriate mixing/ compaction temperatures for asphalt binders based on the applied shear rate and the rheological profile of the binder. © 2018 Taylor & Francis Group, London.